Service composition approaches for internet of things: a review. (29th May 2019) - Aoudia, Idir; Benharzallah, Saber; Kahloul, Laid; Kazar, Okba
The internet of things (IoT) is the integration of information space and physical space, becoming more and more popular in several places. In order to answer the complicated user request, most IoT devices do not work alone, a multiple service composition must be made, and it is defined as the services composition. A number of approaches to IoT's service composition have been proposed in the literature. We have noticed a lack of studies that review the different works of the service composition in IoT. Thereby, in this paper, we present a review of existing approaches for service composition in IoT. It describes and compares them among each other with respect to some criteria, which we have defined based on the different challenges of service composition in IoT. Finally, we conclude by discussing open research issues and avenues for further work.